Introduction to the Case Studies - Lavinia Bifulco (Social Work and Society)
The aim of the following nine case-studies is to enhance understandings of successful ways in which to support young people who encounter difficulties, or who fail, in the 'standard' routes of education and the transition towards employment, by empowering their capabilities for voice, work and education.Â  By applying the capability approach, we have elaborated a perspective which highlights...